1990
DOI: 10.1093/oxfordjournals.eurheartj.a059740
|View full text |Cite
|
Sign up to set email alerts
|

Normal and stenotic human aortic valve opening: in vitro assessment of orifice area changes with flow

Abstract: The ability to measure aortic valve area clinically has emphasized the need to understand the changes in aortic valve orifice area during flow. To compare the performance of normal and stenotic human aortic valves we used a pulsatile flow model that simulated in vivo flow conditions. Five normal autopsy specimens and 15 stenotic valves removed at operation were mounted into the model. Valve function was assessed by analysis of video recordings of valve leaflet motion during flow. Over the flow rates tested nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
3

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 0 publications
1
12
0
3
Order By: Relevance
“…Calculation of MVA by the continuity equation may represent an average of the instantaneous values throughout diastole and thus a better measurement at rest, but it was not used in the present study because of its limitations during tachycardia. In vitro models have suggested that peak MVA cannot be further increased, but the mean valve area can be enhanced simply by acceleration of the opening and closing phases (30). This may result in an increase of the calculated MVA due to an increase in the contraction coefficient, which is the ratio of effective to anatomic valve areas (31).…”
Section: Discussionmentioning
confidence: 99%
“…Calculation of MVA by the continuity equation may represent an average of the instantaneous values throughout diastole and thus a better measurement at rest, but it was not used in the present study because of its limitations during tachycardia. In vitro models have suggested that peak MVA cannot be further increased, but the mean valve area can be enhanced simply by acceleration of the opening and closing phases (30). This may result in an increase of the calculated MVA due to an increase in the contraction coefficient, which is the ratio of effective to anatomic valve areas (31).…”
Section: Discussionmentioning
confidence: 99%
“…9) and showed similar characteristics like the EOA of human aortic valves. 14,22 The slightly asymmetric shape of the closing leaflets of the SJM Epic TM Supra Valve in Fig. 9 at t = 0.28 s might be caused by the sewing of the leaflets into the stent by the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…O método de medida hemodinâmica mais utilizado é a TD, por apresentar maior precisão e estar incorporado na prática clínica por mais tempo 4,6,10 . Já o DTE, apresenta maior simplicidade, porém tem sido mais recentemente incorporado na prática clínica 5 .…”
Section: Discussionunclassified
“…
INTRODUÇÃOEntre os vários métodos disponíveis para a monitoração do débito cardíaco (DC) de pacientes submetidos a procedimentos cirúrgicos ou internados em unidades de terapia intensiva 1-2 , tem encontrado aceitação universal a termodiluição (TD), considerada gold standard na monitoração hemodinâmica [3][4] . Na última década, diversos estudos foram realizados com o objetivo de encontrar métodos simples e pouco invasivos, que permitam determinar com precisão o débito cardíaco 1,5-6 .
…”
unclassified